Intravenous Immunoglobulin (IVIG) Therapy for COVID-19 Omicron (B.1.1.529) Variant with Acute Respiratory Distress Syndrome - Dewi Arum Sawitri; Arie Zainul Fatoni (Faculty of Medicine, Brawijaya University, 2023)
Background: COVID-19 become the pandemic and infect more than million people. The World health organization and other clinical institutions have not yet established a definitive therapy to treat this disease due to a rapid virus mutation and anomaly.Case: A 78-year-old man who had previously confirmed COVID-19 was referred to the COVID-19 intensive care unit (ICU), the patient had geriatrics comorbid, cerebrovascular accident (CVA) infarction, and hypertension. The patient came with unresponsive awareness, and complaints of right hemiparesis and dysarthria. Other symptoms included cough, shortness of breath, and fever. Shortness of breath aggravates, blood pressure increases, and SpO2 was 86%. We decide intubated the patient because have a sign of respiratory distress. Patients receive standard therapy for COVID-19. On the second day, patient receive intravenous immunoglobulin (IVIG) gamaras 20 g. IVIG therapy perform for five days. On the fifth day of treatment in the ICU, the patient’s complaints had decreased and the patient breathed spontaneously with high flow nasal cannula (HFNC).Conclusion: Intravenous immunoglobulin (IVIG) therapy on the COVID-19 Omicron variant patient with ARDS produce a positive outcome. Patients treat with IVIG for 5 days show an improvement in breathing, laboratory result and chest x-ray.